SINTESIS DAN KARAKTERISASI CMC (CARBOXYMETHYL CELLULOSE) YANG DIHASILKAN DARI SELULOSA JERAMI PADI - Nur, Rahman (JURUSAN ILMU DAN TEKNOLOGI PANGAN, UNIVERSITAS HALU OLEO, 2016)
This study aims to investigate the characteristics of CMC (Carboxymethyl Celluolose) produced from rice straw and determine the amount of sodium monochloroasetat needed to produce high purity CMC from rice straw. The treatment of variation of sodium monochloroasetat used for the synthesis of CMC consists of three levels ie the addition of 4 gram, 6 gram and 8 gram. The results of the analysis highest purity of 3 level treatment were analyzed further by analysis of the substitution degree, FTIR, pH and viscosity. CMC Characteristics are the presence of hydroxyl (OH) stretch at 3351.27 cm-1, CH Sp3 at 2917.27 cm-1, carbonyl (C = O) with absorption peaks at 1586.05 cm-1 and group hiroksil (OH) bending at 1411.93 cm-1. The optimum conditions of synthesis reaction of rice straw CMC obtained on addition of 4 gram sodium monochloroasetat with a purity of 98,86%. CMC produced by the addition of 4 gram of sodium monochloroasetat has a substitution degree of 0,31, with pH of 10,55 and a viscosity of 1,44 cp.